Antagonism, accommodation and agonism in critical management studies: alternative organizations as allies - Parker, Simon; Parker, Martin (Sage Publications, 2017)
Critical Management Studies has long been engaged in discussions about the purpose of critique and the possibilities of engagement. A recent expression calls for Critical Management Studies to moderate its ‘negative’ critique of management and instead use words like care, engagement and affirmation in order to enable ‘progressive’ engagement with managers. This ‘performative turn’ has been poorly received by some who see it as a dilution of radical intent. We argue for a middle ground between the antagonistic versions of Critical Management Studies that appear to want to oppose management, and ‘performative’ scholars who appear to accommodate with managerialism. We do this by planting the debate firmly within an empirical setting and a crisis that the first author experienced as a ‘critical scholar’ when conducting an ethnography at a sustainable financial services firm. In order to do this, we explore Chantal Mouffe’s concept of agonism to establish a particular mode of political engagement that acknowledges a space between being ‘for’ and being ‘against’. We conclude by suggesting that the exploration of alternative forms of organization and management, themselves already involved in struggle against a hegemonic present, should be the proper task of a discipline that wishes to engage with the present and remain ‘critical’